New Employee Recruitment Using Web-Based Oreste Method - Nababan, Monica Nababan; Nurhayati, Nurhayati (Marqcha Institute, 2025)
Decisions taken in the long term will affect the quality and performance of the company in the long term. PT. Intan Havea Industry, as a rapidly growing company, faces challenges in selecting candidates who best meet the required criteria. The employee selection process is still subjective and time-consuming, so a system is needed that can support decision making objectively and efficiently. This study aims to design and develop a Decision Support System (DSS) that can help PT. Intan Havea Industry in selecting new employees more effectively and efficiently. The method used in this system is ORESTE (Organization, Ranking, and Evaluation of Socio-Technical and Environmental Factors), which is able to evaluate various relevant criteria in the employee requirements process. The ORESTE method was chosen because of its ability to handle multi-criteria problems and provide objective results based on comparisons between candidates. The system is built web-based, allowing flexible access and can be integrated with various devices. This system accepts input data in the form of assessment criteria for each candidate and interview results, and provides candidate rankings sorted based on the evaluation value of the ORESTE method. System testing shows that this application can provide recommendations for the right candidates based on objective analysis, minimize subjective bias, and speed up the selection process. The results of this study are expected to contribute to the development of a web-based information system that can support more accurate decision making in the employee recruitment process at PT. Intan Havea Industry and other companies. With this system, it is hoped that the employee recruitment proces